The MSC data set - Marasović, Ana; Zhou, Mengfei; Frank, Anette (Universität, 2019)
From this page you can download resources we created for modal sense classification as reported in Zhou et al. (2015), Marasović et al. (2016) and ...
Kind of data: Textual data
Production date: 2015
Gesehen am 09.10.2019
Keywords: Forschungsdaten; Datenbank